Efl Students’ Motivation On Learning English With Authentic Video Project - Abdi Zihan Nanda, Nazriani Lubis (Pusdikra Publishing, 2022)
This study aims to explore the perception of EFL students towards learning English while using authentic video project. Authentic video project is believed as an effective medium to explore and measure students motivation. In this research, a qualitative research method was applied by using thematic analysis. There were 3 students chosen to have the semi structure interview. Based on the result, this research report that there are three theme found, namely: understandable, realistic, wider range of language skill. The students share the same perception that authentic video project leads to the way they learn English skill easily even though the have different English skill level. Also, the students have much opportunity to directly practice through creating the script, practice the pronunciation and listening altogether when making the voice over. Therefore EFL students become more creative in learning English with authentic video project. The result of the study found that using the authentic video project got a fairly good perception that was flexible and quite effective.